Evaluation of tension softening curve of concrete at low temperatures using the incremental displacement collocation method. (1st March 2020) - Fan, Bing; Qiao, Yanmin; Hu, Shaowei
Highlights: 3D-DIC was used to measure the surface deformations of the beams at low temperatures. TSCs of concrete were evaluated. TSCs were verified through displacements, fracture energy and fracture toughness. The inﬂuence of temperature on the fracture and damage properties were presented. Abstract: The three-point bending tests of concrete beams at different temperatures (20 °C, 0 °C, −20 °C, and −40 °C) were carried out by using a low-temperature fracture test system. The digital image correlation technique was utilized to measure the surface displacement and strain fields of the specimens. The crack characteristics, including the crack propagation length and the crack opening displacement profile were determined. The tension softening curves (TSCs) of concrete were obtained using the incremental displacement collocation method. The developed TSCs were verified through the comparisons of the displacements determined by finite element method and by clip gauge as well as the fracture energy. In addition, based on the double-K fracture criterion, the deviations of two fracture toughness were analyzed, and again the accuracy of the TSCs was verified. Finally, the results of characteristic length and damage scale were also presented in this paper.